The Effect of Accounting Information System Utilization, Human Resource Competence, and Internal Audit on the Quality of Financial Statements at OPD Surabaya City Office - Arifin, Annisa Putri; Widajantie, Tituk Diah (International Journal of Business and Applied Economics, 2024)
This study aims to identify the influence of the use of accounting information systems, human resource dumber competence, and internal audit on the quality of financial statements of the City of Surabaya. The sample for this study was taken from the Regional Apparatus Organization (OPD) of Surabaya City, which was used in a quantitative method. The sampling technique was carried out by a simple random sampling method based on probability.  The total number of participants in this study amounted to 100 participants including financial staff. Data analysis techniques using SmartPLS 4.0. The results show that the quality of financial reporting is not significantly affected by the use of accounting information systems. The quality of financial reporting is significantly influenced by the competence of human resources. The quality of financial reporting is significantly affected by internal audit. This study makes a valuable contribution to preserving the caliber of the financial reports of Surabaya's regional apparatus organizations as well as offering prospective assessments for upcoming upgrades.